W- and Mo-based polyoxometalates (POM) as interlayer in Al/n-Si photodiodes - Yenel, Esma; Torlak, Yasemin; Kocyigit, Adem; Erden, Ibrahim; Kus, Mahmut; Yildirim, Murat (SPRINGER, 2021)
W- and Mo-based POM layers were fabricated by a chemical method successfully. The FT-IR and NMR spectrometer were performed to obtain structural behaviors of the W- and Mo-based POMs. SEM and AFM image used to reveal the surface morphologies of the W- and Mo-based POMs. The pinhole and crack-free porous surfaces were obtained. Electrochemical behaviors of the W- and Mo-based POMs were studied a galvanostat. Then, the W- and Mo-based POM layers used as film layer between the Al and n-Si layer to obtain POM interlayered photodiodes Thus, the Al/n-Si (reference), Al/WPOM/n-Si and Al/MoPOM/n-Si photodiodes were fabricated by evaporating of the metallic and ohmic contact in a thermal evaporator. I-V measurements were performed on the photodiodes under dark and various light illumination intensities. The photodiodes exhibited good rectifying properties, but rectifying behavior decreased with POM interlayers and increasing light power intensity. The reverse currents of the Al/n-Si photodiode increased almost 1000 times at 100 mW/cm(2). However, they increased almost 100 times for the Al/WPOM/n-Si and Al/MoPOM/n-Si photodiodes. Whereas the forward currents did not change for Al/n-Si photodiode, they increased with increasing light power in the case of Al/WPOM/n-Si and Al/MoPOM/n-Si photodiodes. Various diode parameters such as ideality factor, barrier height and series resistance values were calculated by various techniques and discussed in details. The detector parameters such as responsivity, photosensitivity and specific detectivity values were accounted and compared for the Al/n-Si, Al/WPOM/n-Si and Al/MoPOM/n-Si photodiodes with increasing light power. The POM interlayered photodiodes and photodetectors can be improved for industrial applications.
Keywords: 2-DIMENSIONAL W-183 NMR; ELECTRICAL CHARACTERISTICS; TEMPERATURE-DEPENDENCE; SERIES RESISTANCE; X-RAY; SCHOTTKY; PERFORMANCE; TIO2; AU/SNO2/N-SI; DERIVATIVES; Engineering; Materials Science; Physics